Differences in clinical and biological factors between patients with PFO-related stroke and patients with PFO and no cerebral vascular events - Badea, Raluca Ştefania; Ribigan, Athena Cristina; Grecu, Nicolae; Terecoasǎ, Elena; Antochi, Florina Anca; Bâldea Mihǎilǎ, Sorina; Tiu, Cristina; Popescu, Bogdan Ovidiu (Frontiers in Neurology, 2023)
Background: While stroke is one of the most dissected topics in neurology, the primary prevention of PFO-related stroke in young patients is still an unaddressed subject. We present a study concerning clinical, demographic, and laboratory factors associated with stroke and transient ischemic attack in patients with patent foramen ovale (PFO), as well as comparing PFO-patients with and without cerebrovascular ischemic events (CVEs). Patients and Methods: Consecutive patients with PFO-associated CVEs were included in the study; control group was selected from patients with a PFO and no history of stroke. All participants underwent peripheral routine blood analyses, as well as, on treating physician’s recommendations, screening for thrombophilia. Results: Ninety-five patients with CVEs and 41 controls were included. Females had a significantly lower risk of CVEs than males (p=.04). PFO size was similar between patients and controls. Patients with CVEs had more often hypertension (n=33, 34.7%), p=.007. No significant differences were found between the two groups with regard to routine laboratory tests and thrombophilia status. Hypertension and gender were identified in a binomial logistic regression model as independent predictors for CVEs, but with an area under the ROC curve of .531, suggesting a very poor level of discrimination between the two groups. Discussion and Conclusions: There is little difference between patients with PFO with and without CVEs in terms of PFO size and routine laboratory analyses. While still a controversial topic in the specialty literature, classic first-level thrombophilic mutations are not a risk factor for stroke in patients with PFO. Hypertension and male gender were identified as factors associated with a higher risk of stroke in the setting of PFO.